Performance Analysis of Polycrystalline and Monocrystalline Solar Modules in Dry-Land Crop Environments of Arachis Hypogaea (Peanut Plants) - Gah, Ade Manu; Tanesab, Julius A.; Roga, Jefri N. (Journal Research of Social Science, Economics, and Management, 2025)
The province of Nusa Tenggara Timur (NTT) is one of the regions in Indonesia that experiences extended periods of sunlight, lasting up to nine months per year, and possesses a large potential area of dry agricultural land, reaching approximately 3.6 million hectares. Based on these conditions, NTT holds significant potential for the development of agrovoltaic systems. Agrovoltaics is a concept that combines agriculture and solar power generation (PLTS) on the same land, allowing for more efficient land use, where solar panels and crops can mutually benefit each other. The performance of solar panels is highly dependent on solar radiation and ambient temperature. As temperature increases, the output power and efficiency of the panels decrease. Various studies have been conducted to control the temperature effects on solar panel performance, such as applying colored films or blocking films on the panel surface, as well as placing vegetation particularly evapotranspirative plants around the panels to improve cooling and efficiency. This study aims to analyze the effect of the dryland crop Arachis hypogaea L. (peanut), as part of an agrovoltaic system, on the output performance of polycrystalline and monocrystalline solar panels. Both panel types were tested with Arachis hypogaea planted beneath them and compared to identical panels without vegetation. The results showed that placing Arachis hypogaea beneath the panels led to a reduction in panel surface temperature, which in turn resulted in an increase in output voltage both Voc (open-circuit voltage) and Vmp (maximum power voltage) for both monocrystalline and polycrystalline panels.